VEGETASI BAWAH DI TEGAKAN TUA COCOS NUCIFERA L (ARECACEAE) DI PULAU PARI, TELUK JAKARTA=(UNDER-GROWTH VEGETATION IN THE OLD COCONUT COCOS NUCIFERA L. (ARECACEAE) STANDS IN THE PARI ISLAND, JAKARTA BAY) - Razali Yusuf; Purwaningsih .; Sukristijono Sukardjo (Jurnal Teknologi Lingkungan, 2010)
Undergrowth vegetation analysis in the old coconut stands in the Pari Island wasundertaken, to determine the structure and floristic composition in relation with their habitat characteristics. Physiognomically, the undergrowth vegetation typified by grasses community with Ischaemum muticum (Importance Value: 122.94%) and Imperata ylindrica (Importance Value:  5.45%) to be a dominant and co-dominant species,respectively. Floristically, the grasses community consists of 27 families along with their 56 genera and 58 species. Amongst those, only 15 species belong to a weed component and can be classified as principal and common weed species in the agricultural land in Indonesia. The grasses community has four common families in term of their highestnumber of species, viz Compositae, Euphorbiaceae, Leguminosae and Poaceae.Based on the ordination technique of Principal Component Analysis (PCA) three distinct groups of the vegetation component can be recognized as (i) pes-caprae formation, (ii)Calophyllum formation and (iii) transition community zone. The spatial distribution of prevalent species in relation with their habitat characters was discussed. Generally, the grasses community can be classified into secondary vegetation of the small island.Keywords : Vegetasi bawah, pohon kelapa, kenanekaragaman jenis, mitigasi,pengelolaan terpadu pesisir dan laut, Pulau Pari, Teluk Jakarta